HASIL BELAJAR IPS TALKING STICK DAN MAKE A MATCH MEMPERHATIKAN MINAT BELAJAR - Yayuk Sulan Utami Ningsih; Pujiati Pujiati; Nurdin Nurdin (FKIP Unila, 2015)
The purpose of this study was to determine the differences in learning outcomes of IPS Terpadu and the interaction between learning model and learning interest. The method used was comparative with experimental approaches. The study population sample were 289 students with a number of 78 students that were determined by cluster random sampling. Hypothesis testing was using two-way analysis of variance formula and t-test of two independent samples. The results showed that: (1) there are differences in learning outcomes of those who used Talking Stick learning model and those students who used Make A Match learning model, (2) learning outcomes of students who were taught by using Talking Stick is higher than Make A Match on student who have high interest in learning , (3) the learning outcomes of students who are taught by using Talking Stick is higher than Make A Match on students who have low interest in learning, and (4) there is an interaction between cooperative learning model with learning interest on learning outcomes.Tujuan penelitian ini untuk mengetahui perbedaan hasil belajar IPS Terpadu serta interaksi antara model pembelajaran dan minat belajar. Metode yang digunakan adalah komparatif dengan pendekatan eksperimen. Populasi penelitian 289 siswa, jumlah sample 78 siswa ditentukan dengan Cluster Random Sampling. Pengujian hipotesis menggunakan rumus analisis varian dua jalan dan t-test dua sampel independen. Hasil penelitian: (1) terdapat perbedaan hasil belajar yang pembelajarannya menggunakan model Talking Stick dan siswa yang pembelajarannya menggunakan Make A Match, (2) hasil belajar siswa yang diajar menggunakan Talking Stick lebih tinggi dibandingkan Make A Match pada siswa yang minat belajarnya tinggi, (3) hasil belajar siswa yang diajar menggunakan Talking Stick lebih tinggi dibandingkan Make A Match pada siswa minat belajarnya rendah, dan (4) ada interaksi antara model pembelajaran kooperatif dengan minat belajar terhadap hasil belajar.Kata kunci: hasil, minat, make a match, talking stick